The Shift of the Slow Tourism Concept During the Period of the Covid-19 Pandemic at Yabbiekayu Eco-Bungalows - Putri, Angela Savina; Widyastuti, Dyah Titisari (Universitas Negeri Yogyakarta, 2024)
Even though it was affected by the Covid 19 pandemic, tourism actors are trying to persist in improving and developing the quality of tourist travel. One way that tourism actors do this is by making changes to the implementation, namely the concept of slow tourism in a tourist trip. The slow tourism concept is a tourism concept that focuses on improving the quality of travel by considering the ecological conditions of the environment, reducing emissions, and the welfare of the surrounding community, so as to create an authentic and unforgettable tourist trip. The study of the concept of slow tourism will not work without complete tourism components consisting of attractions, amenities, accessibility, accommodation and tourist activities. This research will discuss the concept of slow tourism in the tourism component which is the basis for changes in the application of the concept of slow tourism in the period before, during and after the Covid 19 pandemic at Yabbiekayu Eco Bungalows and the Timbulharjo Village area. This research discusses the extent of changes in the application of the slow tourism concept to tourist trips as well as the factors that influence changes to a tourist trip in the period before, during and after the Covid 19 pandemic at Yabbiekayu Eco Bungalows. The method used is descriptive qualitative, by collecting interview and observation data. The results of the research carried out will show the extent of changes in the concept of slow tourism in the period before, during and after the Covid 19 pandemic in Timbulharjo Village with the case study of Yabbiekayu Eco Bungalows. These changes will be identified in accordance with the research time period that has been determined, then a conclusion will be made regarding how dynamic and consistent the changes in the slow tourism concept that occurred during the period before, during and after the Covid 19 pandemic at the research locus, namely at Yabbiekayu Eco Bungalows and in the village Timbulharjo, Bantul, Yogyakarta.